#### Answer

Refer to the graph below.

#### Work Step by Step

Simplify the equation to obtain:
\begin{align*}
y+3x&=6\cdot \frac{1}{2}x -6\cdot 2\\
y+3x&=3x-12\\
y&=3x-12-3x\\
y&=-12
\end{align*}
Recall:
The graph of an equation of the form $y=k$ is a horizontal line that passes through the point $(0, k)$. All points on the line have a $y$-coordinate of $k$, and the graph has no $x$-intercept unless $k=0$.
Thus, the graph of the given line is a horizontal line that passes through $(0, -12)$.
The graph has no $x$-intercept.
Refer to the graph above.